Assessing Sediment Ecological Quality in Organic Shrimp Farming Ponds by Comparing the Shannon-Wiener, AMBI, and M-AMBI Indices - Thai, Tran Thanh; Dang, Le Hai; Quang, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 3, 2018)
The Shannon-Wiener Index (H′), AZTI’s Marine Biotic Index (AMBI) and multivariate AMBI (M-AMBI) of macrofauna communities were applied for comparing their applicability in assessing the status of sediment ecological quality (EcoQ) in eight organic shrimp farming ponds (OSFP) in Ca Mau province. There were obvious differences between the evaluation results of the three indices in the eight OSFP. The EcoQ given by the AMBI and M-AMBI was higher than that given by the H’ index. This indicates that H’ index may also be more sensitive to environmental disturbances than the AMBI and M-AMBI. Furthermore, the EcoQ given by the M-AMBI was a neutralization between those given by the H’ and AMBI indices. As there were no environmental data available in this study, that the H′ index was more sensitive to environmental disturbances than the AMBI and M-AMBI has yet to be further elucidated. Further investigation of these three indices with environmental data is also needed to get a comprehensive answer to this matter. Keywords AMBI, benthic indices, H′, indicator, M-AMBI, macrofauna communities, organic shrimp farming ponds References [1] S. Bustos-Baez, C. Frid, Using indicator species to assess the state of macrobenthic communities, Advances in Polychaete Research, Springer, 2003. [2] C. J. Dauvin, T. Ruellet, N. Desroy, L. A. Janson, The ecological quality status of the Bay of Seine and the Seine estuary: use of biotic indices, Marine Pollution Bulletin 55 (2007) 241. [3] H. Teixeira, S. B. Weisberg, A. Borja, J . A.Ranasinghe, D. B. Cadien, R. G. Velarde, ... & J.K. Ritter, Calibration and validation of the AZTI'sMarine Biotic Index (AMBI) for southern California marine bays, Ecological Indicators 12(2005) 84. [4] I. Muxika, A. Borja, W. Bonne, The suitability of the marine biotic index (AMBI) to new impact sources along European coasts, Ecological Indicators5(1) (2005) 19. [5] R. Pinto, J. Patrício, A. Baeta, Review and evaluation of estuarine biotic indices to assess benthic condition, Ecological Indicators 9(1) (2009) 1. [6] C. E. Pielou, Ecological Diversity. New York: John Wiley and Sons, 165, 1975. [7] A. Borja, J. Franco, V. Pérez, A marine biotic index to establish the ecological quality of soft-bottom benthos within European estuarine and coastal environments, Marine Pollution Bulletin 40(12) (2000) 1100. [8] I. Muxika, A. Borja, J. Bald, Using historical data, expert judgement and multivariate analysis in assessing reference conditions and benthic ecological status, according to the European Water Framework Directive, Marine Pollution Bulletin 55(1–6) (2007) 16. [9] L. Cai, L. Ma, Y. Gao, Analysis on assessing criterion for polluted situation using species diversity index of marine macrofauna, Journal of Xiamen University (Natural Science) (in Chinese) 41(5) (2002) 641. [10] X. Luo, K. Sun, J. Yang,W. Song, W. Cui, A comparison of the applicability of the Shannon-Wiener index, AMBI and M-AMBI indices for assessing benthic habitat health in the Huanghe (Yellow River) Estuary and adjacent areas, Acta Oceanologica Sinica 35(6) (2016) 50. [11] T. T. Tran, Q. X. Ngo, Assessment of the Ecological Quality Status of Sediment in the Organic Shrimp Farming Ponds Using Azti’s Marine Biotic index Based on Macrobenthic Communities, VNU Journal of Science: Natural Sciences and Technology 34(2) 2018 29. [12] A. Borja, M. D. Dauer, A. Grémare, The importance of setting targets and reference conditions in assessing marine ecosystem quality, Ecological Indicators 12(1) (2012) 1. [13] B. Li, Q. Wang, B. Li, Assessing the benthic ecological status in the stressed coastal waters of Yantai, Yellow Sea, using AMBI and M-AMBI, Marine Pollution Bulletin 75(1–2) (2013) 53. [14] W. Cai, A. Borja, L. Liu, Assessing benthic health under multiple human pressures in Bohai Bay (China), using density and biomass in calculating AMBI and M-AMBI, Marine Ecology 35(2) (2014) 180. [15] J. Forde, K. P. Shin, J. P. Somerfield, M-AMBI derived from taxonomic levels higher than species allows Ecological Status assessments of benthic habitats in new geographical areas, Ecological Indicators 34 (2013) 411. [16] A. Borja, D. M. Dauer, R. Díaz, Assessing estuarine benthic quality conditions in Chesapeake Bay: A comparison of three indices, Ecological Indicators 8(4) (2008) 395. [17] L. M. Zettler, D. Schiedek, B. Bobertz, Benthic biodiversity indices versus salinity gradient in the southern Baltic Sea, Marine Pollution Bulletin 55(1–6) (2007) 258. [18] A. Borja, I. Muxika, J. Franco, The application of a Marine Biotic Index to different impact sources affecting soft-bottom benthic communities along European coasts, Marine Pollution Bulletin 46(7) (2003) 835. [19] E. C. Shannon, A mathematical theory of communication, The Bell System Technical Journal 27 (1948) 379. [20] A. Borja, I. Muxika, Guidelines for the use of AMBI (AZTI’s Marine Biotic Index) in the assessment of the benthic ecological quality, Marine Pollution Bulletin 50(7) (2005) 787. [21] A. Borja, A. B. Josefson, A. Miles, I. Muxika, F. Olsgard, C. Phillips, ... & B. Rygg, An approach to the intercalibration of benthic ecological status assessment in the North Atlantic ecoregion, according to the European Water Framework Directive, Marine Pollution Bulletin 55(1-6) (2007) 42. [22] M. Ponti, C. Casselli, M. Abbiati, Applicazione degli indicibiotici all’analisi delle comunita` bentoniche degli ambientilagunari costieri: la ‘Pialassa Baiona’, In: Atti XII Congresso SITE Urbino (2002). [23] R. Rosenberg, M. Blomqvist, S. H. Nilsson, H. Cederwall, A. Dimming, Marine quality assessment by use ofbenthic-abundance distributions: a proposed new protocolwithin the European Union Water Framework Directive, Marine Pollution Bulletin 49 (2004) 728. [24] S. Prato, G. J. Morgana, P. La Valle, M. G. Finoia, L. Lattanzi, L. Nicoletti,... & G. Izzo, Application of biotic and taxonomic distinctness indices in assessing the Ecological Quality Status of two coastal lakes: Caprolace and Fogliano lakes (Central Italy), Ecological Indicators 9(3) (2009) 568. [25] H. Blanchet, N. Lavesque, T. Ruellet, C. J. Dauvin, G. P. Sauriau, N. Desroy, ... & C. Bessineton, Use of biotic indices in semi-enclosed coastal ecosystems and transitional waters habitats—implications for the implementation of the European Water Framework Directive, Ecological Indicators 8(4) (2008) 360.